2014
DOI: 10.1007/s00535-014-1007-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between Wisteria floribunda agglutinin-positive Mac-2 binding protein and the fibrosis stage of non-alcoholic fatty liver disease

Abstract: Serum WFA(+)-M2BP values are useful for assessing the stage of liver fibrosis in patients with NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
188
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(208 citation statements)
references
References 35 publications
10
188
10
Order By: Relevance
“…In addition, WFA + -M2BP is reported to be a reliable marker of hepatic fibrosis and prognosis in patients with primary biliary cirrhosis and nonalcoholic fatty liver disease. 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, WFA + -M2BP is reported to be a reliable marker of hepatic fibrosis and prognosis in patients with primary biliary cirrhosis and nonalcoholic fatty liver disease. 16,17 …”
Section: Introductionmentioning
confidence: 99%
“…Higher qHBsAg level is correlated with both HDV-RNA levels and necroinflammatory activity of hepatocytes in HDV infection [16]. WFA+-M2BP has been reported to be a non-invasive, rapid, useful marker for predicting liver fibrosis in several chronic liver diseases [17][18][19][20]. Yet whether M2BPGi level can be useful for determining liver fibrosis in patients with chronic hepatitis D remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that serum WFA + -M2BP level represents a reliable non-invasive marker for liver fibrosis in patients with chronic hepatitis B, C, non-alcoholic fatty liver disease and primary biliary cirrhosis [17][18][19][20]. Therefore, the aim of this study was to compare qHBsAg and M2BPGi levels between groups of HBsAg carriers with or without HDV infection.…”
Section: Introductionmentioning
confidence: 99%
“…The thorough process selected Mac-2 binding protein (M2BP) with a specific glycoform recognized by WFA. This marker was initially described as WFA-binding M2BP or WFA + -M2BP in earlier studies [19,[48][49][50][51], but renamed as M2BPGi upon commercialization of the diagnostic kit in collaboration with a commercial company. M2BP is a secretory protein of about 90 kDa that presents seven N-glycans per monomer.…”
Section: M2bpgi the Liver Fibrosis Glyco-biomarker For Chronic Hepatmentioning
confidence: 98%
“…. M2BPGi is an effective glyco-biomarker for the evaluation of fibrosis in patients with nonalcoholic fatty liver disease [50]. .…”
Section: Large-scale Validation Of M2bpgi In Clinical Studiesmentioning
confidence: 99%